Authentic Leadership Questionnaire: invariance between samples of Brazilian and Portuguese employees - Cervo,Clarissa S. (2016)
Abstract The Authentic Leadership Questionnaire (ALQ) is used to assess authentic leadership (AL). Although ALQ is often used in empirical research, cross-cultural studies with this measure are scarce. Aiming to contribute to filling this gap, this study assesses the invariance of the ALQ measure between samples of Brazilian (N= 1019) and Portuguese (N= 842) employees. A multi-group confirmatory factor analysis was performed, and the results showed the invariance of the first- and second-order factor models between the Brazilian and Portuguese samples. The results are discussed considering their cultural setting, with the study’s limitations and future research directions being pointed out.